Measuring and Managing Returns from Retailer-Customized Coupon Campaigns - Venkatesan, Rajkumar; Farris, Paul W. (Journal of Marketing, 2012)
The authors assess how and why retailer-customized coupon campaigns affect customer purchases. The conceptual model proposes effects on trip incidence and revenues through the mere exposure to campaigns (exposure effect) and the redemption of coupons (redemption effect). The authors propose monetary savings of the coupons, regularity of the campaigns, and coupon fit with customer preferences as moderators. Analysis of data from a group of regional grocery chains that were part of a quasi experiment demonstrates that retailer-customized coupon campaigns have a positive exposure and redemption effect on customer purchases. Mere exposure to customized coupon campaigns contributes more than coupon redemption to campaign returns. Consistent with theoretical expectations, customized coupon campaigns are more effective if they provide more discounts, are unexpected, and are positioned as specially selected for and customized to consumer preferences. The substantial exposure effects suggest that managers should look beyond redemption rates and also consider sales lift from nonredeemers when measuring the effectiveness of customized coupon campaigns.